Characterising refractive index dispersion in chalcogenide glasses - Fang, Y.; Sójka, L.; Jayasuriya, D.; Furniss, David; Tang, Z.Q.; Markos, C.; Sujecki, S.; Seddon, Angela B.; Benson, Trevor M. (IEEE, 2016)
Much effort has been devoted to the study of glasses that contain the chalcogen elements (sulfur, selenium and tellurium) for photonics’ applications out to MIR wavelengths. In this paper we describe some techniques for determining the refractive index dispersion characteristics of these glasses. Knowledge of material dispersion is critical in delivering step-index fibres including with high numerical aperture for mid-infrared supercontinuum generation.